Grandmaster of demonic cultivation, the comic = Mo dao zu shi. 1 - Moxiangtongxiu (Seven Seas Entertainment, 2022)
"Feared and hated for his sinister abilities, Wei Wuxian-the grandmaster of demonic cultivation-was driven to his death when the most powerful clans united to destroy him. Thirteen years later, Wei Wuxian is reborn. Summoned by a young man who sacrificed his soul in a forbidden ritual, Wei Wuxian is now bound to seek vengeance on the stranger's behalf or risk the destruction of his own soul. But when an evil entity emerges, a familiar face from Wei Wuxian's past suddenly appears amidst the chaos-a powerful cultivator who will help shine a light on the dark truths that surround them. Don't miss this full-color xianxia fantasy manhua/comic from China about two powerful men who are drawn to each other through war and across lifetimes!"--